Correlations of the triglyceride−glucose index and modified indices with arterial stiffness in overweight or obese adults - Tang, Yuchen; Li, Li; Li, Jialin (Frontiers in Endocrinology, 2024)
BackgroundInsulin resistance (IR) contributes substantially to the development of cardiovascular disease (CVD) and metabolic disorders, particularly obesity. The homeostatic model assessment of IR is a prevalent IR indicator, but insulin measurement is quite impractical for widely use. Given its convenience and accessibility, the triglyceride−glucose (TyG) index, along with modified indices such as the triglyceride−glucose−waist circumference (TyG−WC) and triglyceride−glucose−waist−height ratio (TyG−WHtR), are gaining recognition as practical tools for assessing IR. This study aimed to investigate the specific correlation between the TyG index and its modified indices with arterial stiffness in an overweight or obese population and to explore novel, self-defined modified TyG indices for identifying individuals at elevated risk for such conditions.MethodsThis retrospective study included 1,143 overweight or obese individuals from 2021 to 2023. Medical data, including brachial-ankle pulse wave velocity (baPWV), were collected. Two novel modified TyG indices, TyG-1h and TyG-2h, were defined by substituting the fasting glucose level in the TyG formula with 1-hour and 2-hour post-load plasma glucose levels, respectively. Multivariate logistic regression analyses were conducted to identify parameters that demonstrated a statistically significant correlation with arterial stiffness, defined as a baPWV threshold of ≥ 1400 cm/s. Additionally, restricted cubic spline (RCS) modelling was employed to further explore these relationships in a visually interpretable manner. To evaluate and compare the diagnostic accuracy of the conventional TyG index and its novel modified versions, receiver operating characteristic (ROC) curve analyses were performed.ResultsOur findings revealed that individuals with arterial stiffness presented significantly elevated TyG index and all its modified versions (P< 0.05). By utilizing a binary logistic regression model and adjusting for potential confounders, we determined that all TyG-related parameters independently correlated with an increased risk of developing arterial stiffness. Moreover, TyG-WHtR displayed the best correlation (OR 3.071, 95% CI 1.496-6.303) when stratified by quartiles, followed by TyG-1h (OR 2.298, 95% CI 1.248-4.234) and TyG-2h (OR 2.115, 95% CI 1.175-3.807). ROC curves suggested that TyG-1h and TyG-2h demonstrated superior diagnostic performance compared to TyG, with AUCs of 0.685, 0.679 and 0.673, respectively.ConclusionsThe modified TyG indices exhibited strong effectiveness in identifying arterial stiffness in Chinese overweight or obese individuals.